Association between hyperthyroidism and risk of incident in Parkinson's disease. Issue 1 (January 2021) - Lin, Shih-Rong; Chen, Shih-Fen; Yang, Yu-Cih; Hsu, Chung-Y; Shen, Yu-Chih
Abstract : Hyperthyroidism contributes to many other disease conditions, including neurodegenerative diseases. Parkinson's disease (PD) is one of the most common neurodegenerative diseases. The purpose of this study was to investigate the risk of PD in patients with hyperthyroidism. A total of 8788 patients with hyperthyroidism and 8788 controls (without hyperthyroidism) matched by age, gender, index year, and Charlson Comorbidity Index (CCI) score were enrolled between 2000 and 2012. Patients were then followed until the end of 2013 using Taiwan's National Health Insurance Research Database, at which time participants who developed PD were identified. Cox regression analysis was used to calculate the hazard ratio (HR) with a 95% CI of PD incidence rate between patients with hyperthyroidism and unaffected controls. Patients with hyperthyroidism had a significantly increased risk of PD compared with unaffected controls (1.21 vs 0.45 per 1000 person-years, HR: 2.69, 95% CI: 1.08–6.66) after adjusting for age, gender, CCI score, comorbidities, and antithyroid therapy. Hyperthyroidism and PD may share common manifestations. After excluding the first year of observation, a similar result is obtained (HR: 2.57, 95% CI: 1.61–4.01). Also, this study found that older age (HR: 3.74–8.53), more comorbidities (HR: 1.58–1.63), and specific comorbidities (brain injury (HR: 1.57) and cerebrovascular disease (HR: 3.44)) were associated with an increased risk of developing PD. Patients with hyperthyroidism have an increased risk of developing PD. Additional prospective clinical studies are warranted to examine the relationship between hyperthyroidism and PD and determine if there is an intervention that could reduce PD risk.